NUMERICAL ANALYSIS OF BLAST RESISTANT STRUCTURE IN OIL AND GAS PLANT - Rudy, Mohd Taufik (Universiti Teknologi PETRONAS, 2018)
Explosion is one of the major hazards that may be encountered by oil and gas industry. In this research, a numerical analysis of an existing blast resistant building in AAA Refinery plant is done with respect to the maximum possible blast pressure. The analysis is inclusive of the checking of the structural members such as beams, columns and walls. From the outcome of the analysis, it is perceived that the existing structure failed and thus by using the same dimension of the building, a design alternative is provided. The design will ensure that the structure will not be failing in the context of the structural members as well as the whole building itself. By using different arrangement, sizes and reinforcement of the structural members, the structure is designed with the aim of having a blast resistant structure that can sustain the highest possible blast pressure released from surrounding of the building in oil and gas plant.